Parent’s Anxiety Towards Juvenile Deliquency Phenomenon in Bandung, Indonesia - Namirotu Fauziah; Imas Rafiyah; Tetti Solehati (NurseLine Journal, 2018)
Juvenile delinquency is a behavior that can disturb the local people, especially parents who have adolescents. Parents who have adloescents will be more anxious and will treat their child in a overprotective way to keep their child from juvenile delinquency. This study aims to know the level of parental anxiety about juvenile delinquency phenomenon in Babakansari Kiaracondong Bandung.This study used quantitative descriptive method with cross sectional approach. The sample which was taken using proporsionate random sampling technique are 258 respondents. The data collection used State-Trait Anxiety for Adults. The results of this study indicate that in the state anxiety most respondents (55.8%) had moderate anxiety level. Whereas, in trait anxiety almost all respondents (76.0%) had moderate anxiety level.The conclusions in this study that the level of anxiety of parents who have adolescents to the phenomenon of juvenile delinquency in Babakansari village are at moderate level. Based on these results, there should be special attention from the government working with community mental nurses to provide interventions such as emotional control, information about juvenile delinquency and help parents develop their ability to resolve problems related to the anxiety.